2012
DOI: 10.2322/tastj.10.pe_31
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Response Simulation of Ultra Light Weight Phenolic Carbon Ablator by the Use of the Ablation Analysis Code

Abstract: A space vehicle which undergoes the atmospheric re-entry or a planetary entry needs the heat shield system to protect inner equipments against severe aerodynamic heating environments. Charring ablator is usually used for the heat shield system. In order to design the heat shield system, it is necessary to predict the thermal behavior under aerodynamic heating by ablation analysis. A computer code for charring ablation and thermal response analysis is newly developed for simulation of one-dimensional transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Mathematical model of ablation, input data for the ablation analysis and the analysis conditions for the parametric study are shown in the following sections. 10,11) A one-dimensional computer code for charring ablation and thermal response analysis was used to calculate the heat resistant performance of the LATS ablators. The code was developed for simulation of one-dimensional transient thermal behavior of charring materials, and was successfully applied to the LATS ablators under the heating environments of arc-heated test.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mathematical model of ablation, input data for the ablation analysis and the analysis conditions for the parametric study are shown in the following sections. 10,11) A one-dimensional computer code for charring ablation and thermal response analysis was used to calculate the heat resistant performance of the LATS ablators. The code was developed for simulation of one-dimensional transient thermal behavior of charring materials, and was successfully applied to the LATS ablators under the heating environments of arc-heated test.…”
Section: Discussionmentioning
confidence: 99%
“…Cpg and hpyro are assumed to be constant values of 1674.6 J/(kg K) and 3.313�10 5 J/kg, respectively. 10,11) For each time step, output parameters are obtained simultaneously for both the ablator and the backup wall.…”
Section: Mathematical Model Of Ablationmentioning
confidence: 99%
See 3 more Smart Citations